Profit efficiency and economic value added of extended value chain activities in Malaysian plantation companies - Wan Azizi, Wan Noor Elani (2021)
Palm oil industry in Malaysia is the main driver of Malaysia’s agricultural sector due to the significant contribution of this industry towards the Malaysian economy. High demand and attractive earnings of palm oil have attracted high participation in this industry. However, lower palm oil prices have affected the performance of the industry, where, in 2018, the total export revenue of this industry declined sharply by 13.3 percent to RM67.49 billion as compared to the RM77.81 billion in 2017 due to lower global palm oil prices. The decline in palm oil export revenue is reflected in decreasing profits of plantation companies since they are mainly export-oriented with the total profits of 44 plantation companies declining from 53.43 percent in 2017 to 34.25 percent in 2018. This disparity begs the questions as to the ability the plantation companies which is brings to the relevant indicators have includes efficiency and economic value added of plantation companies which provides as the benchmark for performance analysis. Therefore, this study's general objective is to investigate whether extending the value chain activities in plantation companies will improve the profit efficiency and economic value added. In order to attain this objective, this study focus on three important objectives; (i) to assess the profit efficiency of plantation companies involving a different value chain activities; (ii) to investigate inefficiency factors that influence the profit efficiency of plantation companies involving a different value chain activities; (iii) to examine the economic value added and the factors that influence the economic value added of plantation companies involving a different value chain activities. Two methodologies are employed namely Stochastic Frontier Analysis (SFA) and dynamic generalized method of moments (DGMM). The study took a sample of 40 Malaysian plantation companies that listed in Bursa Malaysia. For this study, to achieve the first and second objectives, the sample period spanned 19 years, annually from 2000 to 2018, and for the third objective, the sample period spanned 9 years, from 2010 to 2018. For the first objective, the empirical results indicate that the mean profit efficiency for plantation companies is 60.3 percent. According to the findings, plantation companies' profit efficiency could be increased by 39.7 percent by improving technical, allocative, and scale efficiency. Based on groups, the downstream integrated plantation companies recorded the highest profit efficiency (76.6 percent) than the pure upstream plantation companies (54.2 percent). For the second objective, the value chain activities show significant results in influencing the plantation companies profit efficiency. It is found that the oleochemicals/ biodiesel activities give the highest coefficient, -0.573, followed by plantation activities which is, -0.571, and refineries activities, -0.266. However, other factors, such as ownership, firm’s age, exchange rate, and crude palm oil price, except for mills activities, also significant influence the plantation companies profit efficiency. The empirical analysis for the third objective based on economic value added shows that both downstream integrated activities, namely oleochemicals/ biodiesel and refineries activities are significant influence the plantation companies economic value added, with the coefficient value 1.12 and 0.09 respectively. Other factors such as gross margin, crude palm oil price, and exchange rate also significant influence the plantation companies economic value added. The empirical results based on plantation companies profit efficiency and economic value added are influenced by different value chain activities, as expected. The findings show that the downstream integrated activities like refineries, and oleochemicals/ biodiesel activities play a significant role in increasing the profit efficiency and economic value added of plantation companies. It is also worth noting that, while the percentage of these two activities is not particularly significant, when the number of companies involved in these two types of activities is considered, it is discovered that plantation companies involved in oleochemicals/biodiesel activities are fewer (seven companies) than companies involved in activities (40 companies). As all 40 plantation companies have their own oil palm plantation areas, it is not impossible that plantation activities have a relatively high percentage. These findings revealed that, despite the fact that only a small number of companies were involved in oleochemicals/biodiesel activities, they had the greatest impact on the profit efficiency and economic value added of plantation companies. Plantation companies have consistently played a significant role in Malaysia in the context of economy. From the findings, several recommendations are given to assist plantation companies to enhance their profit as well economic value added. Based on this study, the government, palm oil industry organisations such as Malaysian Palm Oil Board are called for in order to endeavors to encourage the upstream plantation companies ventures in downstream value chain activities by providing more incentives, reducing taxes, and ensuring a more conducive business environment with less bureaucracy.